CONCEPTS OF REGIONALIZATION, REGIONAL SUBSYSTEMS, REGIONAL COMPLEXES AND REGIONAL TRANSFORMATIONS IN CONTEMPORARY IR - Alexei D. Voskressenski (Сравнительная политика)
Abstract: The article examines theoretical aspects of regional dimension in international relations and the ways to apply in practice the results of world politics’ analysis from the viewpoint of regional and macro-regional levels. It also considers the key discussion points on regions and macro-regions in the world and Russian research literature. The author concludes that this is exactly the new IR concepts of regional level which should become the prototype of original Russian regional and country studies. These studies need to have a higher degree of theoretical conceptualization of regional level as their basis. Such an approach will enable the researchers to draw deep and unconventional conclusions of practical use especially as far as the non-Western parts of the world which are traditionally less examined by Western researchers, theorists and practitioners are concerned.